Risk factors of thrombophlebitis at infusion sites in patients admitted in surgical ward: a prospective observational study - Singh, Atul Kumar; Dwivedi, Rajeev; Ghaharwar, A. P. S. (International Surgery Journal, 2018)
Background: Peripheral venous canualation is indispensable in admitted patients in surgical ward, thrombophlebitis following infusion is seldom serious, but it effects on postoperative recovery, hospital stay and hence burden of disease are magnanimous. The main aim and objective of the study to find out the incidence of thrombophlebitis at the intravenous infusion site in surgical ward. Methods: This prospective observational study was conducted on 300 patients admitted in surgical ward of S.S Medical College and associated S.G.M. hospital, Rewa (M.P.) patients selected randomly. These Patients were visited daily for any sign and symptoms at infusion site. The incidence of thrombophlebitis according to age, sex and duration of infusion were recorded. The tool designed to collect the data were socio demographic performa and observational check list. Results: In total 300 patients the incidence of thrombophlebits is highest in age group of 41-50(20%), Male (64.66%) and incidence increases as the duration of infusion increased it is 100% after 5 days. The incidence of Grade -1 thrmbophlebitis (71.33%) is higher as compared to Grade- 2 (22.67%). Conclusions: Thrombophelebitis is still an important ongoing problem in admitted patients in surgical ward. Incidence of grade-I thrombophlebitis is higher. It is more in male in the age group of 40-50 and duration of infusion is main causative factor for development of thrombophlebitis.